2015
DOI: 10.1002/jbt.21719
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of GADD45a on Furazolidone‐Induced S‐Phase Cell‐Cycle Arrest in Human Hepatoma G2 Cells

Abstract: In this study, overexpression of GADD45a induced by furazolidone in HepG2 cells could arouse S-phase cell cycle arrest, suppress cell proliferation, and increase the activities of cyclin D1, cyclin D3, and cyclin-dependent kinase 6 (CDK6). To the opposite, GADD45a knockdown cells by RNAi could reduce furazolidone-induced S-phase cell cycle arrest, increase the cell viability, decrease the activities of cyclin D1, cyclin D3, and CDK6; however, cyclin-dependent kinase 4 (CDK4) showed no change. Moreover, data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…As a cell cycle regulator, RB1 controls cell cycle progression and arrests the cell cycle by repressing E2F target genes [ 29 ]. The GADD45A pathway partially influences S-phase cell cycle arrest in G2 cells via cyclin D1, cyclin D3, and CDK6 [ 30 ]. These results suggest that PGL represses cell cycle-related genes and also activates apoptosis-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…As a cell cycle regulator, RB1 controls cell cycle progression and arrests the cell cycle by repressing E2F target genes [ 29 ]. The GADD45A pathway partially influences S-phase cell cycle arrest in G2 cells via cyclin D1, cyclin D3, and CDK6 [ 30 ]. These results suggest that PGL represses cell cycle-related genes and also activates apoptosis-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…A new discovery has been found whereby GADD45a influenced furazolidone-induced S-phase cell cycle arrest in HepG2 cells via cyclin D1, cyclin D3, and CDK6 [ 19 ]. GADD45a, a member of GADD45 family, have been implicated in the regulation of many cellular functions, including DNA repair, cell cycle checkpoint, signaling transduction and maintenance of genomic stability [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, after UV irradiation, a pronounced S-phase accumulation of GADD45a deficient cells was observed [ 22 ]. Cyclin A and their relative protein are responsible for regulating the cell cycle transition, some relevant signaling pathways activated when the cell cycle arrest in S-phase, which regulates cell death and inhibition of cell proliferation [ 19 , 24 ]. It suggested that apoptosis in HepG2 cells might be suppressed through p38 MAPK and ROS-phosphorylation of JNK pathways in response to olaquindox treatment [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, FZD treatment significantly increased the mRNA level of p53 (Figure 7). Our previous studies had showed that p38 MAPK and GADD45a, a downstream gene of p53, participated in FZD induced cell cycle arrest and apoptosis [51,52]. Another study demonstrated that curcumin protected against 6-hydroxydopamine-induced neurotoxicity through attenuation of p53-mediated apoptosis in the dopaminergic cell line SH-SY5Y [47].…”
Section: Discussionmentioning
confidence: 99%